Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-35 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Salamander-crawling (C, D) in similarity salamander-walking (A, B) of the 10-year-old Nefeli with a spinal cord injury (Th10). In D the bending is disturbed because of the scoliosis and spasticity.